Enhanced EQE of rare earth-doped fluorescent glass by micro-patterning light incident and emission interface for highly efficient white LEDs - Xiaoqing Du; Hong Chen; Xiaohua Lei; Yu Xiong; Xiaoyang Liu (Applied Physics Express)
The total internal reflection at the fluorescent glass–air interface severely limits the external quantum efficiency (EQE) of fluorescent-glass-based light sources. In this work, micro-patterning of the light incident and exit interface of fluorescent glasses was employed to enhance the light coupling efficiency between LED chip and fluorescent glass, as well as the efficiency of light emission into the external space. A highly efficient white light emission with 41% of EQE was obtained by integrating double-sided micro-patterned Ce ^3+ /Dy ^3+ co-doped fluorescent glass with 310 nm LED excitation chip, increasing by 31.5% and 22.53% respectively, as compared to the ones with planar fluorescent glass and single-sided patterned fluorescent glass.